(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2021)
The research seeks to highlight the importance of digital finance in banking by providing financial and banking services and its role in improving the access of financial services to customers at the farthest possible point by using modern technology to finance their needs by granting them cash credits through electronic payment tools to facilitate them and shorten time and effort as well as Low cost, and this cannot be achieved without concerted efforts and the provision of basic infrastructure that includes connecting the Internet to all targeted areas, whether cities or rural areas, as well as distributing the largest possible number of ATMs and sending specialized teams to those areas that develop in customers the culture of digital finance and its importance in Providing all services, especially financial, to enhance and improve the financial inclusion project and work to simplify the procedure for using these devices in order to achieve one of the most important projects in the country, which is financial inclusion so that this service includes all layers of society, so this research presented the concepts of digital finance and the tools used and their importance as well as financial services And the delivery mechanism to achieve the desired goals. One of the most important conclusions reached by the research for digital technology was a major role in accelerating the wheel of financial inclusion of financial services, and the only way to deepen the financial culture of peoples is financial inclusion, as it contributes to increasing their economic and development capabilities. Increasing investment spending in the field of technology and communication networks, in order to reduce the effort and cost in the settlement between branches and provide distinguished and advanced banking services. Then the results were analyzed and hypotheses confirmed.